Urdu Ka Guldasta (Khususi Isha'at) sadabahar (for class 3) - Fouzia ahsan farooqui (Oxford University Press; Pakistan, 2022)
Sadabahar Class 3 is an engaging learning book that offers young students a range of activities, stories, and lessons to foster their academic and personal growth.